(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
In the clinical practice of Palliative and Hospice Care, daily practice and organizational demands often conceal the lack of articulated phenomenological understanding of the significance of frequent death confrontation and its meaning to those who work in the field as healthcare professionals. In this article, I would like to offer an exploration on the experience of actual death encounter and the cardinal phenomenon of being present to the nakedness of a dead body, in line with the overarching theme of our past annual conference of the Society of Existential Analysis. By doing so, I will draw from theory and personal experience alike.